Community Service and Undergraduates’ Social Capital Development - Krista M. Soria (Michigan Journal of Community Service Learning)
The purpose of this study was to examine the effects of community service participation on undergraduates’ social capital development, including whether any potential effects are conditional by students’ race/ethnicity, parents’ or guardians’ education, and social class. I used a propensity score analysis on a multi-institutional sample of students enrolled at 69 colleges and universities in spring 2021 to construct matched pairs of students who did and did not participate in community service (n = 8,964). The results of ordinary least squares regressions suggest that community service has significant and positive effects on students’ social capital development; however, while the results were uniform for students based upon their parents’ or guardians’ education and social class, the results were not uniform based upon students’ race/ethnicity.